INTERACTION BETWEEN Li+ CATION WITH CROWN ETHERS OF Bz15C5, DBz16C5 AND DBz18C6: MOLECULAR MODELING BASE ON MNDO/d SEMIEMPIRICAL METHOD - Harno Dwi Pranowo; Chairil Anwar (Universitas Gadjah Mada, 2003)
The aim of this research is to find information about the substituent effect to the structure of crown ether benzo-15-crown-5 (Bz15C5), dibenzo-16-crown-5 (DBz16C5) and dibenzo-18-crown-6 (DBz18C6), and also crown ether selectivity to coordinate a Li+ metal cation. The presence of substituent could change the conformations flexibility of crown ether during interact with metal cation. In this research semi empirical MNDO/d method was used for calculations. Firstly, geometry optimization was conducted to crown ethers structure using MNDO/d methods. The next steps were running the geometry optimization of complexes between cation Li+ with crown ethers. Data were produced from these calculation are the parameter of crown ether structures, structures of the complexes, and the binding energy of the cation-crown ethers. The presence of electron-withdrawing substituents decreased the binding energy while that of electron-donating one increase the binding energy (value of ΔE more negative). The substituents which are increase the degree of symmetry of the cation-crown ether complexes could give the increase of crown ether selectivity to bind the cation. Selectivity of crown ether to bind the cation depends on the structural match between ionic radii of crown ether cavity (the ion-cavity size concept). Bz15C5 what has higher selectivity to bind Li+ than DBz16C5 and DBz18C6.